2012
DOI: 10.1016/j.quascirev.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Holocene climate change, vegetation history and human impact in the Central Mediterranean: evidence from the Maltese Islands

Abstract: a b s t r a c tHolocene climates and human impact in the Mediterranean basin have received much attention, but the Maltese Islands in the Central Mediterranean, although a pivotal area, have been little researched. Here, sedimentary and palynological data are presented for three cores from the Holocene coastal and shallowmarine deposits of the Maltese Islands. These show deforestation from Pinus-Cupressaceae woodland in the early Neolithic, and then a long, but relatively stable history of agriculturally degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 51 publications
(91 reference statements)
0
43
0
Order By: Relevance
“…4000 cal yr B.P. onward (Carroll et al, 2012;Gambin et al, 2016;Marriner et al, 2012). At the same way, Pavlopoulos et al (2010) recorded early agro-pastoral practices on Skyros Island (only 22,310 ha, Greece) since the Neolithic time (from ca.…”
Section: The Role Of Past Climate Variabilitymentioning
confidence: 89%
See 2 more Smart Citations
“…4000 cal yr B.P. onward (Carroll et al, 2012;Gambin et al, 2016;Marriner et al, 2012). At the same way, Pavlopoulos et al (2010) recorded early agro-pastoral practices on Skyros Island (only 22,310 ha, Greece) since the Neolithic time (from ca.…”
Section: The Role Of Past Climate Variabilitymentioning
confidence: 89%
“…yr B.P. (Beffa et al, 2015;Carroll et al, 2012;Gambin et al, 2016;Tinner et al, 2009) but it was often assumed that climate was the primary driver of vegetation changes whereas anthropogenic impacts seem significant after 4000-3000 cal. yr B.P.…”
Section: The Role Of Past Climate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…1a) provides a key site to study these dynamics in an island context during the Holocene. However, with no peat bogs or lake deposits, suitable sites for palaeovegetation data collection are very limited; notwithstanding this situation some recent research has been carried out on coastal areas (Carroll et al, 2012;Djamali et al, 2012;Fenech, 2007;Marriner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most evidence on sea-level change in the Maltese Islands has been derived from geomorphological, sedimentological, palynological and archaeological markers (e.g. Carroll et al 2012;Marriner et al 2012;Pedley 2011;Furlani et al 2013), but only goes back a few thousand years. In this study, we also use results from Lambeck et al (2011), who reported estimates of sea-level change for the past 20 ka from the south of Sicily, which is geographically proximal to the Maltese archipelago.…”
Section: Regional Settingmentioning
confidence: 99%